Pengembangan Kapasitas Subak CuculanSebagai Wahana Belajar Petani di Desa Pemogan Kecamatan Denpasar Selatan Kota Denpasar - NANDA AGITA SAPUTRI; I GEDE SETIAWAN ADI PUTRA; I MADE SARJANA (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2017)
The Development of Subak of Cuculan Capacity as a Learning Facility for Farmers in the Pemogan Village, the Sub-District of South Denpasar, Denpasar City Capacity development is the process of building the capacity of individuals, groups, or organizations. Subak is a farmer organization in Bali. The study aimed to describe the capacity of Subak Cuculan as a learning facility for farmers, to describe the function of learning facility of farmers in Subak Cuculan, to analyze the relationship between Subak Cuculan capacity and the function of learning facility of farmers in the Subak Cuculan, and to analyze the development of Subak Cuculan capacity as an effective farmer learning facility. The research location was determined in Pemogan Village purposively by the population of 50 people and the sample was 44 people based on the slovin formula and the data were analyzed by descriptive analysis and rank spearman statistical test. Subak Cuculan capacity is classified as moderate category.The function of the farmers' learning facility in Subak Cuculan is classified in the high category. Capacity of Subak Cuculan and the learning facility function in Subak Cuculan have significant relation of 59%. Subak Cuculan capacity building efforts can be analyzed in physical and non-physical form by identifying problems, problem formulation, and finding solutions for problem solving. Subak Cuculan members are expected to be more passionate in carrying out their farming and more active in utilizing the learning facility in Subak Cuculan. It is also expected that good cooperation from all related parties, namely Subak Cuculan farmers, the agricultural extension agents in South Denpasar, and the Department of Agriculture and Horticulture of Denpasar City in the development of capacity of Subak Cuculan as a learning facility for the farmers.